Resilience of Avian Communities to Urbanization and Climate Change: an Integrative Review - McCloy, Michael W. D.; Andringa, R. Keith; Grace, Jacquelyn K. (Frontiers in Conservation Science, 2022)
The concept of ecological resilience is widely used to assess how species and ecosystems respond to external stressors but is applied infrequently at the level of the community or to chronic, ongoing disturbances. In this review, we first discuss the concept of ecological resilience and methods for quantifying resilience in ecological studies. We then synthesize existing evidence for the resilience of avian communities to climate change and urbanization, two chronic disturbances that are driving global biodiversity loss, and conclude with recommendations for future directions. We only briefly discuss the theoretical framework behind ecological resilience and species-specific responses to these two major disturbances, because numerous reviews already exist on these topics. Current research suggests strong heterogeneity in the responses and resilience of bird communities to urbanization and climate change, although community disassembly and reassembly is high following both disturbances. To advance our understanding of community resilience to these disturbances, we recommend five areas of future study (1) the development of a standardized, comprehensive community resilience index that incorporates both adaptive capacity and measures of functional diversity, (2) measurement/modeling of both community resistance and recovery in response to disturbance, (3) multi-scale and/or multi-taxa studies that include three-way interactions between plants, animals, and climate, (4) studies that incorporate interactions between disturbances, and (5) increased understanding of interactions between ecological resilience and socio-ecological dynamics. Advancement in these areas will enhance our ability to predict and respond to the rapidly accelerating effects of climate change and urbanization.